Perlindungan Konsumen Terhadap Produksi Dan Peredaran Barang Yang Tidak Memenuhi Standar - Fendi Setyawan; Yusuf Adiwibowo; dimas wicaksono (Universitas Sriwijaya, 2025)
This research examines consumer protection in the context of non-standard product circulation in Indonesia as a welfare state governed by law. The study focuses on product standardization regulations, consumer protection against non-compliant goods, and the government’s role in supervising product circulation. The research applies a normative juridical method with statutory and conceptual approaches, using library research on primary, secondary, and tertiary legal materials. The findings reveal that although a comprehensive legal framework exists—including the Consumer Protection Law, Law No. 20 of 2014, Government Regulation No. 34 of 2018, and various ministerial regulations implementation still faces challenges such as weak post-market surveillance, regulatory complexity, and high certification costs for SMEs. Consumers are entitled to claim compensation for losses caused by non-standard products; however, public awareness remains limited. The government has established the Integrated Team for Supervising Circulated Goods (TPBB) to enhance monitoring effectiveness, yet systemic reforms are needed through digitalization, data integration, and harmonization with the World Trade Organization’s Technical Barriers to Trade (TBT) Agreement. This study concludes that optimal consumer protection can only be achieved through collaboration between the government, business actors, and consumers in ensuring that products circulating in the market comply with the Indonesian National Standard (SNI).